Computationalism : new directions - Scheutz, Matthias (MIT Press, 2002)
Classical computationalism -- -the view that mental states are computational states -- -has come under attack in recent years. Critics claim that in defining computation solely in abstract, syntactic terms, computationalism neglects the real-time, embodied, real-world constraints with which cognitive systems must cope. Instead of abandoning computationalism altogether, however, some researchers are reconsidering it, recognizing that real-world computers, like minds, must deal with issues of embodiment, interaction, physical implementation, and semantics. This book lays the foundation for a successor notion of computationalism. It covers a broad intellectual range, discussing historic developments of the notions of computation and mechanism in the computationalist model, the role of Turing machines and computational practice in artificial intelligence research, different views of computation and their role in the computational theory of mind, the nature of intentionality, and the origin of language.